Successful and safe long‐term treatment of cerebral aspergillosis with high‐dose voriconazole guided by therapeutic drug monitoring. Issue 1 (9th November 2018) - Cojutti, Pier Giorgio; Merelli, Maria; Allegri, Lorenzo; Damante, Giuseppe; Bassetti, Matteo; Pea, Federico
Abstract : We report the case of a patient who had cerebral aspergillosis after otorhinolaryngologic surgery and who was successfully and safely treated with high‐dose voriconazole (200 mg q6h) for more than 1 year thanks to a TDM‐guided approach coupled with pharmacological review and with genotyping of CYP2C19 polymorphisms. The findings support the idea that personalized medicine based on TDM coupled with the need of avoiding drug–drug interactions may be helpful for maximizing the net benefit (probability of efficacy vs . probability of adverse events) of voriconazole in the management of long‐term treatment of cerebral aspergillosis.